2000
DOI: 10.1007/s002449910041
|View full text |Cite
|
Sign up to set email alerts
|

Antipredatory Behavior as an Index of Heavy-Metal Pollution? A Test Using Snails and Caddisflies

Abstract: The loss of behaviors that organisms use to avoid predation may serve as a sensitive indicator of pollution. We tested the hypothesis that a correlation exists in the field between heavy metal levels and antipredator behaviors. We examined the antipredator behavior of aquatic caddisfly larvae and snails at sites in the Coeur d'Alene basin of Northern Idaho which varied in their levels of heavy metals. We tested the antipredator response of Physella columbiana snails at 10 polluted lakes downstream from the Bun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Because the number of snails was limited and the egg laying experiment was set up after the results of the climbing experiment were known (no significant effect of crushed snail extract), we did not include a crushed snail extract treatment. Past experience (Lefcort et al 2000(Lefcort et al , 2002 has indicated that many snails have a very strong "all or nothing" response to snail extract. Every day, five drops of treatment solution were placed in each container.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Because the number of snails was limited and the egg laying experiment was set up after the results of the climbing experiment were known (no significant effect of crushed snail extract), we did not include a crushed snail extract treatment. Past experience (Lefcort et al 2000(Lefcort et al , 2002 has indicated that many snails have a very strong "all or nothing" response to snail extract. Every day, five drops of treatment solution were placed in each container.…”
Section: Methodsmentioning
confidence: 98%
“…No anesthesia other than cooling was used, since the anesthesia may have altered the behavior of test snails. Both the snail extract and the fecal solution were filtered (see Lefcort et al 2000). Each snail was exposed to each of the four treatments on separate days; and the order of treatments was randomized.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More subtle changes involve indirect effects of metals in species interactions and community function, resulting from alterations in the physiology and/or behaviour of the various organisms. For example, metal exposure affected the territorial behaviour in hydropsychid larvae, relaxing the levels of interspecific competition (Vuori 1994), causing benthic invertebrates to be more susceptible to predation (Clements et al 1989;Clements 1999;Kiffney 1996;Lefcort et al 2000) and increasing the mortality rate of parasitized amphipods and snails (Brown and Pascoe 1989;Guth et al 1977). However, these effects are likely to vary among populations, communities, and ecosystems in different geographical areas.…”
Section: Effects Of Low Ph and Ecotoxic Metalsmentioning
confidence: 97%